DETEKSI DINI FAKTOR RISIKO PENYAKIT TIDAK MENULAR (STROKE, DENGAN MENGGUNAKAN APLIKASI ERDANELA) PADA JAMAAH SURAU ZAM-ZAM PAGAMBIRAN KOTA PADANG - Riki Nova; Erdanela Setiawati; Sri Wahyuni; Muhammad Ivan (Nusantara Hasana Journal, 2023)
Non-communicable diseases (NCDs) are the biggest cause of death globally and continue to increase. One of the efforts to overcome NCDs in Indonesia is early detection of NCD risk factors in the community, one of which is through health promotion programs. Basic Health Research Data (RISKESDAS) for 2020 shows that the prevalence of stroke in Indonesia in the population aged >15 years is 10.8% or an estimated 2,120,326 people. The prevalence of stroke in West Sumatra is 12.2% (2,553,200 people). Preventive efforts to reduce the number of stroke sufferers are an effective and efficient way. The aim of assessing the level of stroke risk in each resident in the Surau Zam Zam Pagambiran area is predominantly elderly, so it is necessary to prevent strokes in order to minimize the number of strokes in the community environment. Therefore, early prevention will be more effective if each individual knows the risk factors for stroke. One way to prevent early stroke is by using the ERDANELA model stroke prevention service which is able to identify the level of stroke risk. Extension through direct lectures by instructors from the community service team; the media used are power point and questionnaires; The counseling participants consisted of congregants at the Zam-Zam surau, all of whom were elderly (aged 60 years and over) totaling 21 people. Before the counseling, data was filled in and health checks were carried out for each congregation at the Zam-Zam surau (height, blood pressure, blood sugar and cholesterol levels). Of the 21 elderly congregation participants at Pagambiran surau zam-zam in Padang City who took part in counseling on early prevention of stroke risk factors using the Erdanela model troke prevention service, it was found that the congregation participants were very enthusiastic about participating in all series of event activities, with many questions being asked to the material giving committee, and the participants of the Zam-Zam surau congregation understood the material provided and were able to answer all the questions on stroke risk factors given during the question and answer session correctly. Health promotion to the elderly regarding the prevention of non-communicable diseases and early detection at Surau Zam-Zam Pagambiran aims to increase the knowledge of the Surau Zam-Zam Pagambiran congregation regarding the importance of knowing what risk factors can increase the occurrence of stroke through non-communicable diseases. The results of this activity are expected to be able to understand and independently play an active role in implementing healthy living habits by avoiding risk factors for stroke through non-communicable diseases.